A new association between Ornithodoros saraivai (Acari, Argasidae) and a species of rock frog in the genus Thoropa (Amphibia, Cycloramphidae) in Brazil. Issue 2 (3rd April 2018) - Sá-Hungaro, Iwine J. B.; Luz, Hermes R.; Silva, Hélio R.; Famadas, Kátia M.
ABSTRACT: The relationship between argasid ticks and cycloramphid frogs has only recently been described together with the description of new species of ticks, as is the case of Ornithodoros saraivai Muñoz-Leal & Labruna 2017. The type host of this recently described species is the rock frog, Cycloramphus boraceiensis Heyer, 1983. The basic knowledge regarding the use of host by these ticks is still incipient. Here in, we investigated of, a similar host, Thoropa taophora (Miranda-Ribeiro, 1923), also cycloramphid, a rock frog, that may be syntopic to C. boraceiensis and may serve as host to the same species of tick. We surveyed 270 specimens of T. taophora from a Brazilian herpetological collection in search of parasitism by species Ornithodoros . In these samples we found that 49 (18.15%) of the frogs were parasitized by 130 larvae of O. saraivai . The parasitized specimens of T. taophora were from three localities in the state of São Paulo: two continental and one isular. The dates associated with the frog specimens in the collection suggest that the parasite–host relationship is not incidental; the sample includes specimens collected at least five decades ago. This result represent the first record of O. saraivai parasitizing anurans of the genus Thoropa Cope, 1865.